Lithium ion battery composite diaphragm material and preparation method thereof
The modified glass fiber separator is modified by UiO crystal to form a GF@UiO composite separator material, which solves the problems of poor thermal stability and low ionic conductivity of the separator of lithium-ion batteries, and significantly improves the electrochemical performance and safety performance of the battery.
Patent Information
- Application Number
- CN202411531437.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-14
AI Technical Summary
The separators of existing lithium-ion batteries have poor thermal stability and low ionic conductivity, resulting in poor electrochemical and safety performance.
The modified glass fiber diaphragm is modified by UiO crystal to improve its ionic conductivity and lithium ion migration number to form a GF@UiO composite diaphragm material.
It significantly improves the comprehensive electrochemical performance and safety performance of lithium-ion batteries, including improving ionic conductivity, enhancing thermal stability and improving electrochemical performance.
Smart Images

Figure CN119447694A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemical energy storage materials, and specifically relates to a lithium ion battery composite diaphragm material and a preparation method thereof. Background Art
[0002] Lithium-ion batteries (LIBs) have the advantages of relatively light weight, high energy density, long cycle life, strong adaptability to high and low temperatures, no memory effect, and green environmental protection. They are widely used in high-performance energy storage devices in electric vehicles, electronic devices, and aerospace fields. While developing and applying high-energy-density LIBs, the safety issues of LIBs have also attracted people's attention and research. Among the components of LIBs, the safety performance is mainly determined by the properties of the electrolyte and the diaphragm material. The properties of the LIBs diaphragm determine the interfacial resistance during the operation of LIBs, and its compatibility with the positive and negative electrode materials of LIBs and the microscopic interface structure determine the cycle stability of LIBs, and have a substantial impact on the capacity and safety performance of LIBs. Currently, most commercial LIBs diaphragms are single-layer polyolefin diaphragms, such as single-layer PP, single-layer PE diaphragms, or multi-layer composite polyolefin diaphragms, such as three-layer PP / PE / PP diaphragms. The preparation process for producing polyolefin separators is mostly unidirectional or bidirectional stretching, which results in uneven pore distribution inside the separator and low ion conductivity (0.66mS cm-1), resulting in reduced ion transmission efficiency. In addition, polyolefin separators have a low melting point (PP melting point is about 165℃, PE melting point is about 135℃), poor thermal stability, and will melt when the temperature approaches the melting point, resulting in the closure of the separator, preventing Li+ from passing through the separator, causing LIBs to stop working. Although polyolefin separators have thermal blocking properties, the battery will continue to heat up after the diaphragm is closed, and the separator may shrink or even melt, eventually causing the battery to short-circuit, posing a safety hazard. Poor ion transmission performance and thermal stability have greatly limited the application and development of polyolefin separators in high energy density LIBs. Therefore, it is of great significance to develop functional composite separators with high ionic conductivity and thermal stability. Summary of the invention
[0003] The purpose of the present invention is to overcome the above defects and provide a lithium ion battery composite diaphragm material and a preparation method thereof, which solves the technical problems of poor thermal stability, low ionic conductivity, and poor comprehensive electrochemical performance of traditional polyolefin diaphragms in the prior art. The present invention effectively improves the ionic conductivity and lithium ion migration number of the glass fiber (GF) diaphragm substrate through UiO crystal modification, which can effectively improve the comprehensive electrochemical performance and safety performance of lithium ion batteries.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a GF@UiO composite diaphragm material having high ionic conductivity, high thermal stability and excellent electrochemical comprehensive performance, as well as a preparation method and use thereof. UiO crystals are prepared by different synthesis methods, and are grown in situ on a glass fiber diaphragm to achieve a functionalized effect of modifying the diaphragm substrate. The rich pore structure and large specific surface area of the UiO crystal can effectively regulate the ion transmission process, adsorb small impurity molecules generated in the electrochemical reaction process, and slow down the decomposition effect of the electrolyte. The functionalized composite diaphragm effectively improves the comprehensive electrochemical performance and safety performance of lithium-ion batteries.
[0006] The present invention provides a method for preparing a composite diaphragm material for a lithium ion battery, comprising:
[0007] S1 uses an inorganic metal salt compound, an organic ligand, a crystal modulator and a solvent as raw materials to prepare a UiO precursor solution; the inorganic metal salt compound is a chlorinated metal salt, and the metal in the chlorinated metal salt includes one or more of Ti, Zr, Hf or Ce; the organic ligand includes one or more of 1,4-terephthalic acid, 4,4'-biphenyldicarboxylic acid or 4,4'-terphenyldicarboxylic acid and homologues thereof; the crystal modulator includes one or more of formic acid, acetic acid, hydrochloric acid or phenylacetic acid; the solvent includes one or more of methanol, ethanol, N,N-dimethylformamide, N,N-dimethylacetamide or N,N-diethylformamide.
[0008] S2 uses UiO precursor solution and glass fiber diaphragm to obtain GF@UiO composite diaphragm material, that is, lithium-ion battery composite diaphragm material.
[0009] Furthermore, in step S1, in the UiO precursor solution, the molar ratio of the inorganic metal salt compound, the organic ligand and the crystal modulator is 1:1:250-1:1:350; the concentration of the inorganic metal salt compound is 0.008-0.012 mol·L -1 .
[0010] Furthermore, in step S1, the inorganic metal salt compound, the organic ligand, the crystal modulator and the solvent are ultrasonically mixed to obtain a UiO precursor solution;
[0011] The ultrasonic mixing time is 30-60 minutes, the temperature is 20-30°C, and the power is 100-300W.
[0012] Further, in step S2, the GF@UiO composite diaphragm material is obtained by diffusion synthesis method, which specifically includes:
[0013] The UiO precursor solution was transferred to a conical flask with a glass fiber diaphragm, the conical flask was covered with a glass dish, and heated to 90-110° C. for 10-20 days to obtain a GF@UiO composite diaphragm material.
[0014] Further, in step S2, the GF@UiO composite membrane material is obtained by a solvent thermal synthesis method, which specifically includes:
[0015] The UiO precursor solution is transferred to a polytetrafluoroethylene reactor, a glass fiber diaphragm is placed in the polytetrafluoroethylene reactor, and the UiO precursor solution and the glass fiber diaphragm in the reactor are subjected to a solvothermal reaction at 100-150° C. for 24-48 hours to obtain a GF@UiO composite diaphragm material.
[0016] Further, in step S2, a GF@UiO composite diaphragm material is obtained by a microwave-assisted heating method, which specifically includes:
[0017] The UiO precursor solution was transferred to a polytetrafluoroethylene reactor, a glass fiber diaphragm was placed in the polytetrafluoroethylene reactor, the reactor was placed in a microwave synthesizer, the microwave power was set to 700-900 W, the UiO precursor solution and the glass fiber diaphragm in the reactor were reacted at 125-175° C. for 20-40 min, and a GF@UiO composite diaphragm material was obtained.
[0018] Further, in step S2, the GF@UiO composite diaphragm material is obtained by a continuous flow method, which specifically includes:
[0019] The UiO precursor solution was extracted by two independent pumps and heated and mixed at a temperature of 120-140°C in the coil reactor. The heated and mixed solution was passed through a back pressure regulator at a pressure of 80-100 mL min -1 The synthetic reaction flow rate flows into a closed container containing the glass fiber diaphragm, and after reacting for 24 to 48 hours, the GF@UiO composite diaphragm material is obtained.
[0020] Furthermore, the glass fiber separator is in the shape of a disc, with a diameter of 25-55 mm and a thickness of 260-675 μm.
[0021] Furthermore, the above-mentioned method for preparing a lithium-ion battery composite diaphragm material further includes:
[0022] S3 ultrasonically cleans, dries, and cuts the obtained GF@UiO composite diaphragm material into pieces.
[0023] A lithium-ion battery composite diaphragm material is obtained by using the above-mentioned preparation method of a lithium-ion battery composite diaphragm material, wherein the surface loading amount of UiO crystals on the surface of the glass fiber diaphragm in the GF@UiO composite diaphragm material is 0.001 mg·mm-2 ;
[0024] The pore size of the GF@UiO composite membrane material is 2.80-3.00 nm, and the BJH adsorption cumulative pore volume is 0.20-0.30 cm 3 ·g -1 , Langmuir specific surface area is 1000-1100m 2 ·g -1 ;
[0025] The ionic conductivity of GF@UiO composite membrane material is 6.0-7.0 mS·cm -1 , lithium ion migration number t Li+ It is 0.80-0.90.
[0026] Compared with the prior art, the present invention has at least one of the following beneficial effects:
[0027] (1) The present invention creatively proposes a method for preparing a composite separator material for lithium-ion batteries, which effectively improves the ionic conductivity and lithium ion migration number of a glass fiber (GF) separator substrate by modifying UiO crystals, and can effectively improve the comprehensive electrochemical performance and safety performance of lithium-ion batteries;
[0028] (2) The present invention adopts different synthesis methods to prepare UiO crystals, thereby improving the uniformity of in-situ growth of UiO crystals on the glass fiber diaphragm, so as to achieve the functionalization effect of modifying the diaphragm substrate;
[0029] (3) In the existing inventions, most of the UiO precursor solutions use a specific crystal modulator, which has a narrow application range and is not conducive to practical application. The present invention provides a formula of the UiO precursor solution, wherein the crystal modulator includes formic acid, acetic acid and its homologues, which can provide a weak acid environment H + All organic acids in the atmosphere can achieve catalytic effects on synthetic reactions;
[0030] (4) The present invention adopts a variety of methods to prepare GF@UiO composite membrane materials. Among them, the MOF crystal microstructure and morphology obtained by microwave-assisted heating method are more dense and uniform than those obtained by other methods, and its morphology structure can be adjusted according to the microwave power. The performance difference between different samples is small, the synthesis time is short, and the synthesis efficiency and success rate are high. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 11 is a scanning electron microscope image of the GF@UiO-66-NH2 composite membrane prepared at different temperatures in Example 1, Example 2, and Example 3 of the present invention; wherein, (a) is a SEM image of the GF@UiO-66-NH2 composite membrane prepared at 100°C magnified 200 times, (b) is a SEM image of the GF@UiO-66-NH2 composite membrane prepared at 100°C magnified 1000 times, (c) is a SEM image of the GF@UiO-66-NH2 composite membrane prepared at 100°C magnified 5000 times, (d) is a SEM image of the GF@UiO-66-NH2 composite membrane prepared at 110°C magnified 200 times EM image, (e) is a SEM image of the GF@UiO-66-NH2 composite membrane prepared at 110°C magnified 1000 times, (f) is a SEM image of the GF@UiO-66-NH2 composite membrane prepared at 110°C magnified 5000 times, (g) is a SEM image of the GF@UiO-66-NH2 composite membrane prepared at 120°C magnified 200 times, (h) is a SEM image of the GF@UiO-66-NH2 composite membrane prepared at 120°C magnified 1000 times, (i) is a SEM image of the GF@UiO-66-NH2 composite membrane prepared at 120°C magnified 5000 times;
[0032] Figure 2 This is a graph comparing the rate performance of GF@UiO-66 composite diaphragms prepared at different temperatures in Example 1, Example 2, and Example 3 of the present invention;
[0033] Figure 3 It is a graph comparing the electrochemical impedance spectra of the GF@UiO-66 composite membrane prepared in Example 3 of the present invention, the PP membrane in Comparative Example 1, and the GF membrane in Example 2 in the ionic conductivity test;
[0034] Figure 4 This is a graph comparing the cycle performance of lithium metal half-cells assembled using the GF@UiO-66 composite diaphragm prepared in Example 3 of the present invention, the PP diaphragm in Comparative Example 1, and the GF diaphragm in Comparative Example 2 matched with NCM811 positive electrode material and metal lithium negative electrode material. DETAILED DESCRIPTION
[0035] The following detailed description of the present invention will make the features and advantages of the present invention more clear and explicit.
[0036] The word "exemplary" is used exclusively herein to mean "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as preferred or advantageous over other embodiments. Although various aspects of the embodiments are shown in the drawings, the drawings are not necessarily drawn to scale unless otherwise noted.
[0037] In view of the problem that the high crystallinity and interface resistance of polyvinylidene fluoride in the prior art will cause adverse capacity attenuation, the present invention provides a lithium-ion battery composite diaphragm material and a preparation method thereof, specifically a GF@UiO composite diaphragm material and a preparation method thereof and use in a lithium battery.
[0038] Glass fiber (GF) separator has high ionic conductivity (9mS cm -1 ) and high thermal stability (melting point is about 680℃), it has become a widely studied type of battery separator in recent years. However, its high interfacial impedance and unsatisfactory electrochemical performance hinder its widespread application in the field of lithium-ion batteries.
[0039] In order to ensure that the electrochemical performance of the glass fiber diaphragm is further improved on the basis of high ionic conductivity and thermal stability, it is necessary to modify the diaphragm substrate. Metal organic framework MOFs (Metal organic Frameworks) materials are a class of porous crystalline compounds self-assembled by metal clusters and organic ligands through coordination bonds. Its three-dimensional porous network structure usually uses metal ions as connection points and organic ligands as supporting structures to form a three-dimensional extension system in space. MOFs materials have high crystallinity, rich pore structure, large porosity, high specific surface area, high thermal stability, excellent designability and functional properties. By using MOFs materials to modify the glass fiber diaphragm, its ion transport performance and electrochemical performance can be further improved. Therefore, the preparation of functionalized composite diaphragm materials with high ionic conductivity, high thermal stability and excellent electrochemical performance has broad application prospects. The UiO (University of Oslo) series of MOF materials were first synthesized and named by the Lillerud research group. They have outstanding high-temperature thermal stability and chemical stability. The crystal structure can remain stable at 500°C, and the crystal skeleton structure can withstand a mechanical pressure of 1.0MPa. It can maintain structural stability in common solution systems such as water, DMF (N,N-dimethylformamide), benzene or acetone. It has excellent chemical stability and is an ideal material for lithium-ion battery separator modification.
[0040] The present invention comprehensively utilizes the advantages and characteristics of glass fiber (GF) diaphragm and MOFs materials, and adopts a variety of synthesis methods to prepare GF@UiO composite diaphragm materials with excellent ion transmission performance, high temperature thermal stability and comprehensive electrochemical performance.
[0041] The present invention provides a method for preparing a lithium-ion battery composite diaphragm material, specifically a method for preparing a GF@UiO composite diaphragm material, comprising the following steps:
[0042] S1. Preparation of UiO precursor solution:
[0043] An inorganic metal salt compound, an organic ligand, a crystal modulator, and a solvent are mixed and uniformly mixed by ultrasonication to obtain a UiO precursor solution;
[0044] S2. A plurality of methods are used to prepare the GF@UiO composite diaphragm material, including the following steps:
[0045] Prepared by diffusion synthesis method: the UiO precursor solution prepared in S1 was transferred to a conical flask with a glass fiber diaphragm, the conical flask was covered with a glass dish, and heated to 90-110°C for 14 days to obtain the GF@UiO composite diaphragm material;
[0046] Prepared by solvothermal synthesis: The UiO precursor solution prepared in S1 was transferred to a polytetrafluoroethylene reactor, and a commercial glass fiber diaphragm was placed in the reactor. The solvothermal reaction was carried out in an electric heated air drying oven at a reaction temperature of 100-150°C and a reaction time of 24h to obtain a GF@UiO composite diaphragm material.
[0047] Preparation by microwave-assisted heating method: The UiO precursor solution prepared in S1 was transferred to a polytetrafluoroethylene reactor, and a commercial glass fiber diaphragm was placed in it. The microwave-assisted heating reaction was carried out in a microwave synthesizer. The reaction temperature was 125-175°C, the reaction time was 30 minutes, and the microwave power was 800W to obtain the GF@UiO composite diaphragm material;
[0048] Prepared by continuous flow method: The independent solution of UiO reactant prepared in S1 was pumped into the coil reactor through two independent pumps for heating and mixing, and finally flowed into a closed container soaked with a glass fiber diaphragm through a back pressure regulator. The heating temperature was 120-140 °C and the synthesis reaction flow rate was 90 mL min -1 , the reaction time is 24h, and the GF@UiO composite diaphragm material is obtained;
[0049] S3. Ultrasonic cleaning, drying and cutting of the prepared GF@UiO composite diaphragm material.
[0050] In a specific embodiment, the molar ratio of the inorganic metal salt compound, the organic ligand, and the crystal modulator is 1:1:3000, and the amount of solvent is adjusted according to the amount of reactants, and the concentration of the inorganic metal salt and the organic ligand reactants is controlled at 0.01 mol·L -1 .
[0051] In a specific embodiment, the inorganic metal salt compound is selected from one of Ti salt, Zr salt, Hf salt and Ce salt.
[0052] In a specific embodiment, the inorganic metal salt compound is selected from metal chloride salts.
[0053] In a specific embodiment, the organic ligand is selected from carboxylic acid ligands such as 1,4-terephthalic acid, 4,4'-biphenyldicarboxylic acid, 4,4'-terphenyldicarboxylic acid, and their derivatives.
[0054] In a specific embodiment, the crystal modulator is selected from formic acid, acetic acid, hydrochloric acid, phenylacetic acid and the like, which have the functions of promoting the nucleus formation of MOFs materials and regulating the crystal growth rate.
[0055] In a specific embodiment, the solvent is selected from one of methanol, ethanol, N,N-dimethylformamide, N,N-dimethylacetamide and N,N-diethylformamide.
[0056] In a specific embodiment, the ultrasonic mixing is performed for 30-60 min, at a temperature of 20-30° C., and at a power of 100-300 W.
[0057] In a specific embodiment, the solvent described in S1 is selected from N,N-dimethylformamide.
[0058] In a specific embodiment, in the ultrasonic mixing described in S1, the washing solvent for ultrasonic cleaning is 99.5% anhydrous methanol.
[0059] In a specific embodiment, the commercial glass fiber separator described in S2 is disc-shaped with a diameter of 25-55 mm and a thickness of 260-675 μm, preferably with a diameter of 25 mm and a thickness of 260 μm.
[0060] In a specific embodiment, when preparing by diffusion synthesis method, the conical flask is heated to 100° C. and kept warm for 14 days.
[0061] In a specific embodiment, when prepared by solvent thermal synthesis, the solvent thermal reaction temperature is 120° C. and the reaction time is 24 hours.
[0062] In a specific embodiment, during microwave-assisted heating, the reaction temperature is 150°C, the reaction time is 30 minutes, and the microwave power is 800W.
[0063] In a specific embodiment, the continuous flow heating temperature is 130°C and the synthesis reaction flow rate is 90 mL·min -1 , the reaction time is 24h.
[0064] In a specific embodiment, the surface loading of UiO crystals on the glass fiber diaphragm is 0.001 mg·mm -2 .
[0065] In a specific embodiment, in S3, the drying is carried out at 80° C. for 5 h in an electric heated forced air drying oven.
[0066] In a specific embodiment, the prepared GF@UiO composite membrane is assembled into a half-cell for electrochemical performance testing.
[0067] The present invention also relates to a GF@UiO composite diaphragm material prepared by the above-mentioned method for preparing a lithium ion battery composite diaphragm material, wherein the ionic conductivity is 6.0-7.0 mS·cm -1 , lithium ion migration number t Li+ The pore size of the obtained GF@UiO composite membrane is 2.80-3.00 nm, and the BJH adsorption cumulative pore volume is 0.20-0.30 cm 3 ·g -1 , Langmuir specific surface area is 1000-1100m 2 ·g -1 .
[0068] The present invention effectively improves the ionic conductivity and lithium ion migration number of the glass fiber (GF) diaphragm substrate by modifying the UiO crystal. The ultra-high specific surface area of the UiO crystal itself and the constructed adjustable porous ion channel improve the ion transport performance of the composite diaphragm, which is conducive to long-cycle stability.
[0069] The present invention also relates to the application of the above-mentioned GF@UiO composite diaphragm material in lithium ion batteries, and is applied to lithium batteries.
[0070] In a specific embodiment, the lithium battery is a liquid lithium metal battery.
[0071] The present invention adopts different synthesis methods to prepare UiO crystals, which are grown in situ on a glass fiber diaphragm to achieve the functionalization of the diaphragm substrate, and then the mechanical and electrochemical stability of the composite diaphragm is further improved by polymer coating modification. The rich pore structure and large specific surface area of the UiO crystal can effectively regulate the ion transmission process, adsorb small impurity molecules generated in the electrochemical reaction process, and slow down the decomposition effect of the electrolyte. The functionalized composite diaphragm effectively improves the comprehensive electrochemical performance and safety performance of lithium-ion batteries.
[0072] Embodiment 1:
[0073] Weigh 141.75 mg of 99.9% ZrCl4, 109.5 mg of 99.32% 2-aminoterephthalic acid, 10.83 g of 99.5% acetic acid and 63.8 mL of 99.9% N,N-dimethylformamide in a beaker and mix ultrasonically for 30 minutes. After cooling, pour into the reactor, then put the cleaned and dried glass fiber diaphragm into the reactor, place the sealed reactor in an electric blast drying oven, and react at 100°C for 24 hours. When the hydrothermal reactor reaction is completed and cooled to room temperature, take out the GF@UiO-66 composite membrane, transfer it to a beaker, pour 100 mL of 99.5% anhydrous methanol, ultrasonically clean it for 30 minutes, and repeat the cleaning step 3 times. Then place the cleaned GF@UiO-66 composite membrane in an electric blast oven and dry it at 80°C for 5 hours, and then transfer it to a vacuum drying oven and vacuum dry it at 90°C for 10 hours. After all the drying steps are completed, the dried composite membrane is taken out and cut into button cell membranes with a diameter of 19 mm using a cutting machine, and then collected in a sealed bag for storage. GF@UiO-66-NH2 (UiO-66-NH2 is a material with Zr-coordinated metal and 2-aminoterephthalic acid as ligand) prepared at 100°C. The microstructure of the composite membrane is shown in Figure 2. Figure 1 As shown in (a), (b) and (c).
[0074] Figure 1 (a), (b), and (c) are scanning electron microscope images of the GF@UiO-66 composite membrane prepared at 100°C in Example 1. It can be observed from the figure that the UiO-66 crystals are partially agglomerated, the interface of the crystals is not clear enough, the octahedral morphology of some crystals is not complete, the overall size of the crystals is different, and the crystallinity is low.
[0075] Figure 2 The electrochemical test results show that the GF@UiO-66 composite separator prepared at 100°C is assembled with NCM811 material as the positive electrode and lithium metal as the negative electrode. The discharge capacity is 180.64 mAh g at 0.2C and 2.8-4.25V. -1 Specific rate performance parameters are shown in Table 1.
[0076] Embodiment 2:
[0077] Similar to Example 1, the difference is that the hydrothermal reaction temperature is 110°C, and the reaction time is also 24h. When the hydrothermal reactor reaction is completed and cooled to room temperature, take out the GF@UiO-66 composite diaphragm, clamp it into a beaker with tweezers, pour in 100mL of 99.5% anhydrous methanol, ultrasonically clean it for 30min, and repeat the cleaning step 3 times. After that, the cleaned GF@UiO-66 composite diaphragm is placed in an electric heating blower and dried at 80°C for 5h, and then transferred to a vacuum drying oven and vacuum dried at 90°C for 10h. After all drying steps are completed, take out the dried composite diaphragm, cut the composite diaphragm into button battery diaphragms with a diameter of 19mm with a cutting machine, and collect them in a sealed bag for storage. The microstructure of the GF@UiO-66 composite diaphragm prepared at 110°C is as follows Figure 1 As shown in (d), (e) and (f).
[0078] Figure 1 (d), (e), and (f) are scanning electron microscope images of the GF@UiO-66 composite membrane prepared at 110°C in Example 2. It can be observed from the figure that compared with the UiO-66 crystals obtained in Example 1, the crystals in Example 2 have a weak agglomeration phenomenon, while the crystal size is more uniform, the crystallinity is significantly increased, the distribution on the glass fiber is denser, and the octahedral outline of the crystal is clearer.
[0079] Figure 2 The electrochemical test results show that the GF@UiO-66 composite membrane prepared at 110°C is used as the positive electrode with NCM811 material and metal lithium as the negative electrode to assemble the lithium half-cell. Under the conditions of 0.2C and 2.8-4.25V, its discharge capacity is 163.86mAh·g -1 Specific rate performance parameters are shown in Table 1.
[0080] Embodiment 3:
[0081] Similar to Example 1, the difference is that the hydrothermal reaction temperature is 120°C, and the reaction time is also 24h. When the hydrothermal reactor is finished and cooled to room temperature, take out the GF@UiO-66 composite membrane, clamp it into a beaker with tweezers, pour in 100mL of 99.5% anhydrous methanol, ultrasonically clean it for 30min, and repeat the cleaning step 3 times. After that, the cleaned GF@UiO-66 composite membrane is placed in an electric blower and dried at 80°C for 5h, and then transferred to a vacuum drying oven and vacuum dried at 90°C for 10h. After all drying steps are completed, take out the dried composite membrane, cut the composite membrane into button battery membranes with a diameter of 19mm with a cutting machine, and collect them in a sealed bag for storage. The microstructure of the GF@UiO-66 composite membrane prepared at 120°C is as follows Figure 1 As shown in (g), (h), and (i).
[0082] Figure 1 (g), (h), and (i) are scanning electron microscope images of the GF@UiO-66 composite membrane prepared at 120°C in Example 3. It can be observed from the figure that compared with the UiO-66 crystals obtained in Examples 1 and 2, the crystal outline in Example 3 is the sharpest and clearest, the growth and coating on the glass fiber is better, the distribution is more uniform, and the agglomeration phenomenon is significantly reduced.
[0083] Figure 2 The electrochemical test results show that the GF@UiO-66 composite separator prepared at 120°C is assembled with NCM811 material as the positive electrode and lithium metal as the negative electrode. The discharge capacity is 183.46 mAh g at 0.2C and 2.8-4.25V. -1 Specific rate performance parameters are shown in Table 1.
[0084] Table 1 Electrochemical properties of GF@UiO-66 composite membranes prepared at different temperatures in Examples 1-3
[0085]
[0086] Comparative Example 1:
[0087] The commercial polyolefin (PP) separator was ultrasonically cleaned with 99.7% anhydrous ethanol for 30 minutes, and then the cleaned polyolefin separator was placed in an electric heating blower to dry at 80°C for 5 hours, and then transferred to a vacuum drying oven to vacuum dry at 90°C for 8 hours. After all the drying steps were completed, the dried composite separator was taken out, and the composite separator was cut into button battery separators with a diameter of 19 mm using a cutting machine, and collected in a sealed bag for storage.
[0088] Figure 3 Electrochemical impedance spectra of SS||SS batteries equipped with different separators; Figure 4 The NCM811||Li half-cell cycle performance diagram equipped with different separators. The results show that the ionic conductivity of the commercial polyolefin (PP) separator is 0.66mS·cm -1 , lithium ion migration number t Li+ The discharge capacity of a commercial polyolefin (PP) separator with NCM811 as the positive electrode and lithium metal as the negative electrode is 213.2 mAh g at 0.2C and 2.8-4.3V. -1 The specific electrochemical performance parameters are shown in Table 2.
[0089] Comparative Example 2:
[0090] The commercial glass fiber (GF) separator was ultrasonically cleaned with 99.7% anhydrous ethanol for 30 minutes, and then the cleaned glass fiber separator was placed in an electric heating blower to dry at 80°C for 5 hours, and then transferred to a vacuum drying oven to vacuum dry at 90°C for 8 hours. After all the drying steps, the dried composite separator was taken out, and the composite separator was cut into button battery separators with a diameter of 19 mm using a cutting machine, and collected in a sealed bag for storage.
[0091] Figure 3 Electrochemical impedance spectra of SS||SS batteries equipped with different separators. Figure 4 The results show that the ionic conductivity of the commercial glass fiber (GF) separator is 9mS·cm -1 , lithium ion migration number t Li+ The discharge capacity of a commercial glass fiber (GF) separator, NCM811 material as the positive electrode and lithium metal as the negative electrode in a lithium half-cell is 199.1 mAh g at 0.2C and 2.8-4.3V. -1 The specific electrochemical performance parameters are shown in Table 2.
[0092] Table 2 Electrochemical properties of different diaphragms prepared in Example 3 and Comparative Examples 1-2
[0093]
[0094] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
[0095] The contents not described in detail in the specification of the present invention belong to the common knowledge of those skilled in the art.
Claims
1. A method for preparing a composite diaphragm material for a lithium-ion battery, characterized in that: include: S1 uses inorganic metal salt compounds, organic ligands, crystal modulators and solvents as raw materials to prepare UiO precursor solution; The inorganic metal salt compound is a chlorinated metal salt, and the metal in the chlorinated metal salt includes one or more of Ti, Zr, Hf or Ce; the organic ligand includes one or more of 1,4-terephthalic acid, 4,4'-biphenyldicarboxylic acid or 4,4'-terphenyldicarboxylic acid and their homologues; the crystal modulator includes one or more of formic acid, acetic acid, hydrochloric acid or phenylacetic acid; the solvent includes one or more of methanol, ethanol, N,N-dimethylformamide, N,N-dimethylacetamide or N,N-diethylformamide. S2 uses UiO precursor solution and glass fiber diaphragm to obtain GF@UiO composite diaphragm material, that is, lithium-ion battery composite diaphragm material.
2. The method for preparing a composite diaphragm material for a lithium-ion battery according to claim 1, characterized in that: In step S1, in the UiO precursor solution, the molar ratio of the inorganic metal salt compound, the organic ligand and the crystal modulator is 1:1:250-1:1:350; the concentration of the inorganic metal salt compound is 0.008-0.012 mol·L -1 .
3. The method for preparing a composite diaphragm material for a lithium-ion battery according to claim 1, characterized in that: In step S1, an inorganic metal salt compound, an organic ligand, a crystal modulator and a solvent are ultrasonically mixed to obtain a UiO precursor solution; The ultrasonic mixing time is 30-60 minutes, the temperature is 20-30°C, and the power is 100-300W.
4. The method for preparing a lithium-ion battery composite diaphragm material according to claim 1, characterized in that: In step S2, a GF@UiO composite diaphragm material is obtained by a diffusion synthesis method, which specifically includes: The UiO precursor solution was transferred to a conical flask with a glass fiber diaphragm, the conical flask was covered with a glass dish, and heated to 90-110° C. for 10-20 days to obtain a GF@UiO composite diaphragm material.
5. The method for preparing a composite diaphragm material for a lithium-ion battery according to claim 1, characterized in that: In step S2, a GF@UiO composite membrane material is obtained by a solvent thermal synthesis method, which specifically includes: The UiO precursor solution is transferred to a polytetrafluoroethylene reactor, a glass fiber diaphragm is placed in the polytetrafluoroethylene reactor, and the UiO precursor solution and the glass fiber diaphragm in the reactor are subjected to a solvothermal reaction at 100-150° C. for 24-48 hours to obtain a GF@UiO composite diaphragm material.
6. The method for preparing a composite diaphragm material for a lithium-ion battery according to claim 1, characterized in that: In step S2, a GF@UiO composite membrane material is obtained by a microwave-assisted heating method, which specifically includes: The UiO precursor solution was transferred to a polytetrafluoroethylene reactor, a glass fiber diaphragm was placed in the polytetrafluoroethylene reactor, the reactor was placed in a microwave synthesizer, the microwave power was set to 700-900 W, the UiO precursor solution and the glass fiber diaphragm in the reactor were reacted at 125-175° C. for 20-40 min, and a GF@UiO composite diaphragm material was obtained.
7. The method for preparing a composite diaphragm material for a lithium-ion battery according to claim 1, characterized in that: In step S2, a GF@UiO composite diaphragm material is obtained by a continuous flow method, which specifically includes: The UiO precursor solution was extracted by two independent pumps and heated and mixed at a temperature of 120-140°C in the coil reactor. The heated and mixed solution was passed through a back pressure regulator at a pressure of 80-100 mL min -1 The synthetic reaction flow rate flows into a closed container containing the glass fiber diaphragm, and after reacting for 24 to 48 hours, the GF@UiO composite diaphragm material is obtained.
8. The method for preparing a composite diaphragm material for a lithium-ion battery according to claim 1, characterized in that: The glass fiber separator is in the shape of a disc with a diameter of 25-55 mm and a thickness of 260-675 μm.
9. The method for preparing a composite diaphragm material for a lithium-ion battery according to claim 1, characterized in that: Also includes: S3 ultrasonically cleans, dries, and cuts the obtained GF@UiO composite diaphragm material into pieces.
10. A lithium-ion battery composite diaphragm material, characterized in that: The method for preparing a lithium ion battery composite diaphragm material according to any one of claims 1 to 9 is used to obtain a GF@UiO composite diaphragm material in which the surface loading amount of UiO crystals on the surface of the glass fiber diaphragm is 0.001 mg·mm -2 ; The pore size of the GF@UiO composite membrane material is 2.80-3.00 nm, and the BJH adsorption cumulative pore volume is 0.20-0.30 cm 3 ·g -1 , Langmuir specific surface area is 1000-1100m 2 ·g -1 ; The ionic conductivity of GF@UiO composite membrane material is 6.0-7.0 mS·cm -1 , lithium ion migration number t Li+ It is 0.80-0.90.
Citation Information
Patent Citations
Production of metal-organic frameworks
CN107614097A
Normal-pressure preparation method of zirconium metal-organic framework material UIO-66
CN111333851A
Hierarchical pore UiO-66 material as well as preparation method and application thereof
CN111690144A
Metal-organic-framework (MOF) coated composite seaparators for electrochemical devices and applications of same
US20200220136A1